Avaliação dos efeitos deletérios do diuron e de seus metabólitos em lambaris (Astyanax sp.): testes de toxicidade, marcadores de estresse oxidativo, marcadores genotóxicos e enzimas de biotransformação - Sanches, Ana Leticia Madeira [UNESP] (2014)
Diuron is a pesticide used in the agriculture and its transformation in potential toxic compounds can be harmful to aquatic ecosystem and animals. This work had as main objective discover if the metabolites 3-(3,4-dichlorophenyl)-3-methylurea (DCPMU), 3,4- dichlorofhenylurea (DCPU) and 3,4-dichloroaniline (DCA) produced in the diuron degradation may cause more or less effects than the pesticide in genotoxic and biochemistry parameters in fish. Toxicity tests were performed with the diuron and its metabolites to obtain the LC50. We observed that the diuron and the DCA have similar toxicity to fish observed by the low values of LC50. The DCPMU LC50 is twice higher and DCPU is three times higher than diuron and DCA. It indicating that these metabolites can be less toxic than the others compounds. From LC50 values, fish exposures were performed at LC1 (0.015 mg/L) and LC10 (0.15 mg/L) of diuron concentration by two and seven days. The genotoxicity was measured by comet assay and we observed that the degradation of diuron increase the genotoxic effects, whereas the DCA, DCPMU and DCPU are able to promote DNA damage. Biochemistry parameters were measured by analysis of biotransformation enzymes (EROD and GST), antioxidant defenses (SOD, GPx and CAT) and lipid peroxidation (MDA). EROD activity is increased after all metabolites exposure in both tissues. GST activity is inhibited after DCA gill exposure and DCPMU and DCPU gill and liver exposures. GST activity also is increased after DCA exposure in liver. SOD is induced in all metabolites treatment and GPx to DCPMU and DCPU exposure. CAT activity is increased after DCA exposure and it is inhibited after DCPMU and DCPU exposures in both tissues. CAT is also inhibited after diuron exposure in the liver. The exposure of diuron and its three main metabolites can change biochemistry parameters indicators of oxidative stress in Astyanax sp. in the conditions tested in this study. In general, the ...